Characterization of relaparotomies performed at the Dr. Gustavo Aldereguía Lima General University Hospital (2015-2017) - Jorge Ernesto Gonzalez García; Mayquel Monzón Rodriguez; Lidia Torres Ajá; Dianelys Molina Macías (Medisur)
Background: Relaparotomies are associated with a considerable percentage of morbidity and mortality in patients who require intensive care; and around this procedure it is complex to decide when and how to do it, so that it is effective in every way. For this reason, the study of its results through the analysis of specific variables is of interest. Objective: to characterize the behavior of relaparotomies in a General Surgery service. Methods: descriptive, longitudinal and prospective observational study, which included patients who required relaparotomies, which were performed in the Surgery service of the Dr. Gustavo Aldereguía Lima General University Hospital General, in Cienfuegos, from January/2015 to December / 2017. The variables analyzed were: operative diagnosis at reintervention, surgical strategy, number of reintervention, and time elapsed from initial surgery to reintervention, among others. Results: a relaparotomy index of 2.7 was obtained. The group over 60 years old and the male sex predominated; peritonitis and postoperative eviscerations were the main causes. The clinical criteria were the most used for reintervention; On-demand relaparotomy was applied to a greater number of patients, compared to the other surgical strategies. Mortality increased in reoperated patients in the first 72 hours. Conclusion: In the series analyzed, the number of reoperations and mortality showed a direct proportionality relationship. Multiple organ dysfunctions were the cause of death most associated with the relaparotomy procedure.